Legal Protection for Company Internship Participants Who Do Not Obtain Their Rights - Khyatudin, Khyatudin; Haq, Rifqi Arroiqul (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
This research examines legal protection for company interns who do not receive their rights. The purpose of this research is to analyze what types of legal protection can be obtained for interns when their rights cannot be fulfilled by the company, as well as to analyze the legal consequences that must be held accountable by companies that have been found to have violated the rights of interns. In completing this research the author used normative research methods. The results of the research show that the regulations governing the rights of apprenticeship participants are very clearly regulated in the laws in force in Indonesia, namely in Law no. 13 of 2003 concerning Employment and Regulation of the Minister of Manpower No. 6 of 2020 concerning the Implementation of Domestic Apprenticeships. However, in reality, in the field, many apprentices and companies do not clearly understand and implement these regulations, which is what causes many cases of exploitation and abuse against apprentices. One of the cases that is the source of the author's research is in Decision Number: 111/Pdt.Sus-PHI/2019/PN.JKT.PST. Apart from regarding the rights of apprentices, the results of the research also show that companies must bear the legal and social impacts that they have to face when they are found unable to fulfill and violate the rights of apprentices. These legal and social impacts include sanctions based on applicable law, cancellation of apprenticeship agreements, threats to the company's reputation and prohibitions on participating in apprenticeship programs held by the government.